KLASIFIKASI WILAYAH RAWAN PANGAN DI KABUPATEN ACEH UTARA MENGGUNAKAN ALGORITMA K-NEAREST NEIGHBOR - Eva Darnila; Maryana Maryana; Khairunnisa Khairunnisa (Politeknik Bisnis Indonesia, 2023)
Food insecurity is a condition where food security is not achieved, so food insecurity can be interpreted as a condition of not providing enough food for individuals or individuals to be able to live healthy, active, and productive lives sustainably The Department of Agriculture and Food of North Aceh Regency has compiled a map of the FSVA of North Aceh Regency but it is known that the process of collecting and summarizing FSVA data takes a long time thus resulting in slow handling. This study classifies regional data to classify food insecurity priorities quickly and efficiently using the K-Nearest Neighbor (KNN) algorithm. The data used in this study were 852 regional data. Then it is grouped into 6 priorities, namely Priority 1, Priority 2, Priority 3, Priority 4, Priority 5, Priority 6. The data is divided into 2, namely 70% is used for training data and 30% is used as test data. The results of the classification of food insecure areas using the K-Nearest Neighbor algorithm are Priority 1 consisting of 7 villages (2.73%), Priority 2 consisting of 24 villages (9.37%), Priority 3 consisting of 4 villages (1.56%) with the Euclidean Distance approach, this study achieved an accuracy rate of 86%.